FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS SUMBER DAYA MANUSIA TERHADAP SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) - Fauziah, Sifa; Dety Mulyanti (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
Human resources (HR) as a very vital hospital asset that has an important role in managing and managing it. Human resources are very functional so they cannot be replaced by other resources. Technical HR support is one of the keys to the success of implementing HMIS in a sustainable and quality manner. The purpose of this literature review is to examine the factors that influence the quality of human resources on the quality of hospital management information systems (HMIS). This literature review used articles in the PubMed, Google Scholar, and ProQuest databases published in 2018-2023, obtained 792 articles which were then reviewed using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) diagram and obtained 6 articles that met the requirements for analysis. . The results of 6 articles obtained that the factors that influence the quality of human resources on the quality of the hospital management information system (HMIS) are factors of education, knowledge, skills, professionalism, organization, technology, and quality of health services. It can be concluded that the quality of human resources certainly has benchmarks that can be influenced by several factors that must be owned by individuals such as knowledge, education, and technology that can support the level of success and indicators in managing hospital management information systems that can produce workers to become more effective and efficient